Structural relationships among mouse and human immunoglobulin VH genes in the subgroup III. - Ollo, R (1983)
The mouse VHIII subgroup is composed of four families which share sequence homology. We isolated a VH germ-line genomic clone, which cross hybridizes with a cDNA probe from one of these families, derived from a myeloma secreting an antigalactan antibody. We report here the nucleotide sequence of the cross hybridizing gene and show that very likely it has an anti-sheep red blood cell specificity. Comparison of its nucleotide sequence with those of the three other VHIII families shows that these genes share segmental homologies of variable lengths. This suggests that interchanges of sequence blocks between VH genes could be an important evolutionary mechanism for diversifying the germ-line repertoire. The strong homology (82%) with human VHIII genes suggests that efficient antibody sequences are strongly conserved. This conservation of homology is particularly striking when compared to the more limited homology (63%) between mouse and human C kappa genes.